Barangay-Led Interventions for CICL: Current Practice and Ways Moving Forward - Lim, Lester John; Lamberte, Hazel Cometa- (Asean Social Work Journal, 2025)
This study examines the barangay-led interventions for Children in Conflict with the Law (CICL) in the three barangays in Quezon City, Philippines, under Republic Act 9344. Using a multiple-case study design, data were collected through semi-structured interviews with 12 key stakeholders, direct field observations, and document analysis to examine how developmental, preventive, and remedial programs are integrated across intervention levels. Findings show that while barangays implement a range of programs for CICL, these tend to be programmatic rather than child-centered. The study found that the local government unit, through the Barangay Council for the Protection of Children (BCPC), implements primary interventions centered on community development, including advocacy initiatives, curfew enforcement, security enhancement, and budget allocation for child protection programs. On the other hand, the secondary interventions involved direct engagement with children through structured dialogues, case management, educational support, counseling, parent education, and organized developmental activities aimed at strengthening protective factors and mitigating delinquent activities. Tertiary interventions that were implemented aimed to address legal concerns by facilitating monitoring, conducting feedback sessions, and implementing reintegration strategies to support CICL while also preventing recidivism. The study highlights the importance of a well-functioning BCPC and recommends capacity-building initiatives, professional practice enhancement, and policy reforms to strengthen community-based, child-focused interventions facilitated by social workers and paraprofessionals.